Hubungan Teman Sebaya dengan Karakter Kewarganegaraan Peduli Sosial Siswa di SMA Negeri 1 Banjarmasin - Noerani Noerani; Rabiatul Adawiah (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to find out the picture of the relationship between students' peers, the description of the character of citizenship and social care of students, and the relationship between the two variables in students at SMA Negeri 1 Banjarmasin. This study uses a quantitative approach with a correlational method. The research sample was 177 students out of a total population of 316 students, which was determined using a simple random sampling technique based on the slovin formula with an error rate of 5%. The data collection used was a Likert scale questionnaire to measure both variables, documentation, and interviews. Data analysis was carried out with descriptive statistics and Spearman correlation test using SPSS version 25. The results of the study showed that the relationship between students' peers and the character of students' social care citizenship were both in the high category. The results of the Spearman correlation test showed a correlation coefficient value (rho) of 0.499 with a significance value of 0.000 < 0.05, so it can be concluded that the research hypothesis is accepted. This means that there is a positive and significant relationship between peers and the character of social care citizenship of students at SMA Negeri 1 Banjarmasin with the strength of the relationship that is classified as moderate based on interpretation guidelines. Based on the results of the research, it is recommended to the school to improve character development and create a positive social environment for students.